Раритетна компонента флори Ківерцівського національного природного парку «Цуманська Пуща» - Іванців, Оксана Ярославівна; Іванців, Василь Володимирович; Ivantsiv Oksana Ya.; Ivantsiv, Vasyl V. (Луцький національний технічний університет, 2015)
У статті розглянуто раритну компоненту флори Ківерцівського національного природного парку «Цуманська Пуща». На території національного природного парку, яка є центром фіторізноманіття південної частини Українського Полісся виявлено види, що підлягають охороні, вони представлені тут одним видом із Європейського червоного списку, І – із додатка 1 Бернської конвенції, 19 – із Червоної книги України, 12 – із обласного списку рідкісних видів. Також охарактеризовано види флори за категоріями рідкісності.

On the basis of the results of the reserches of populations of some rare species of flora Kivertsi National Park "Tsumanska Forest" analyzed the viability of their populations and conservation perspectives. Particular attention was focused on the study of the viability of populations of rare species of European Red List Silene lithuanica Zapat. Besides identification of prospects for further research in this study area. Also set, and other protected species that grow on the territory of Kivertsi National Park "Tsumanskaya Forest" (indicating the growth places), which is the center phytodiversity in the southern part of Ukrainian Polissya 1 - from Annex 1 of the Berne Convention, 19 - from the Red Book of Ukraine , 12 - from the regional list of endangered species population that should be investigated. Also oharakteryzyrovanы types florы by category protection.
Vintage components flora plants Kivertsi National Park "Tsumanska Forest"
Keywords: флора Ківерцівського національного природного парку «Цуманська Пуща»; види, що охороняються; рідкісні види; рекреаційний потенціал; flora Kivertsy National Park "Tsumanska Pusha"; Protected species; rare species; recreational potential